2010
DOI: 10.1007/s00066-010-2065-x
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation in Prostate Radiotherapy up to 82 Gy Using Simultaneous Integrated Boost

Abstract: SIB enables dose escalation up to 82 Gy with a lower rate of gastrointestinal toxicity grade 3 in comparison with 3D-CRT up to 74 Gy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…; Dolezel et al . ) and one abstract (Kirichenko et al . ) were identified, as shown in Table of Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…; Dolezel et al . ) and one abstract (Kirichenko et al . ) were identified, as shown in Table of Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) techniques for prostate cancer facilitate safe dose escalation through maximization of the therapeutic ratio with proven benefits on local recurrence and biochemical control rates [1,2]. Given the very conformal nature of IMRT treatment plans, accurate patient positioning utilizing image-guidance systems is of the utmost importance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the importance of dose escalation in the radiotherapeutic management for various prognostic groups of prostate cancer [2,7,8,11,33]. Intensity-modulated radiation therapy (IMRT) allows the delivery of the necessary high tumor total doses without increasing the dose to the organs at risk [13].…”
Section: Introductionmentioning
confidence: 99%